Teaching Vocabulary by Using Crossword Puzzle - Puspita, Nurul; Sabiqoh, Nurlaily (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research is about teaching vocabulary by using crossword puzzle at the first semester of the seventh grade students of MTs. The objective of this research are to describe process of teaching vocabulary by using crossword puzzle, to describe the teacher’s problems and students’ problem in teaching and learning process. In this research, the researcher used descriptive qualitative research. The researcher used purposive sampling technique to determine the sample. The researcher chose class VII C as sample which consisted of 30 students. In collecting the data, the researcher used three kinds of instruments, they are: observation, interview, and questionnaire. The researcher used three major of data analysis: they were data reduction, data display and conclusion drawing or verification. From the data analysis, the researcher found in teaching vocabulary by using crossword puzzle at MTs were as follows: The first, the teaching and learning process by using crossword puzzle was running well, the classroom atmosphere was the students looked active in classroom but some of them looked less response. The second, the teacher got some problems. They were: The teacher had difficulties to handling the class because the students made over-crowded by themselves, faulty method of teaching, and demand to share some words of vocabulary in meeting but the students only could master some of them. The third, the students got some problems in learning vocabulary, they were : the students consider the teacher’s explanation boring, and they think of vocabulary learning as knowing the primary meaning of new words that are gotten only from textbooks or from the teacher, so it is difficult for them to use the words based on the appropriate context.